2016
DOI: 10.1002/alr.21886
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interpersonal traits on patient outcomes in the treatment of chronic rhinosinusitis

Abstract: BACKGROUND Patient reported outcome measures (PROMs) measure health states in chronic rhinosinusitis (CRS) and have become the dominant metrics of treatment outcomes. Interpersonal traits (IPTs) are patient-specific factors that include personality type, perceived social support, and trust in physicians. The association of IPTs on treatment outcomes among patients with CRS has not been previously described and IPTs may represent important clinical factors influencing treatment outcomes. METHODS Adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The institutional review board (IRB) at each enrollment center provided annual study review and regulatory oversight for all study protocols. Additional findings from this investigation have been described previously …”
Section: Methodssupporting
confidence: 66%
“…The institutional review board (IRB) at each enrollment center provided annual study review and regulatory oversight for all study protocols. Additional findings from this investigation have been described previously …”
Section: Methodssupporting
confidence: 66%
“…In one previous study, CRS patients received the highest scores in the conscientious domain, but there was no statistically significant association between personality traits and patient reported outcome measures such as SNOT-22, PHQ-2, and the Medical Outcomes Study Short Form-6D (SF-6D) after endoscopic sinus surgery. 18 Other studies of otolaryngic complaints have shown that the burden of a subjective symptom, such as tinnitus, is highly correlated with neuroticism as well as anxiety and depression. 35 Anxiety and depression have been shown to be associated with many different aspects of CRS disease burden including more lost productivity and decreased QOL, as well as worse post-operative outcomes.…”
Section: Associations With Activity Avoidancementioning
confidence: 99%
“…15 Recently, the impact of personality and emotional well-being on CRS outcomes and productivity has been of interest. [16][17][18][19] Previous studies have demonstrated that certain personality traits are associated with improved ability to perform activities of daily living (ADLs) and various health-related behaviors. 20,21 Similarly, others have illustrated a relationship between certain personality traits and anxiety, depression, and substance use disorders, as well as pain.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, limited data suggest that although patients often support physician‐industry relationships because they are likely to benefit most from improved drug and device development, patients also believe that they should have access to information regarding potential conflicts of interest 3 . Our patients’ perspectives on such conflicts are paramount: not only is trust essential to establishing a meaningful and productive doctor‐patient relationship, but having a trusted doctor actually improves patients’ health outcomes as well 4,5 . As physicians, it is essential that patients trust that our recommendations are exclusively for their benefit, and it is reasonable for patients to expect access to information regarding our potential conflicts which could influence those recommendations.…”
Section: Viewpointmentioning
confidence: 99%